Increased burst‐firing of ventral tegmental area dopaminergic neurons in d‐amino acid oxidase knockout mice in vivo. (5th July 2014) - Schweimer, Judith V.; Coullon, Gaelle S. L.; Betts, Jill F.; Burnet, Philip W. J.; Engle, Sandra J.; Brandon, Nicholas J.; Harrison, Paul J.; Sharp, Trevor
Abstract d‐Amino acid oxidase (DAO) degrades the N‐methyl‐d‐aspartate (NMDA) receptor co‐agonist d‐serine, and is implicated in schizophrenia as a risk gene and therapeutic target. In schizophrenia, the critical neurochemical abnormality affects dopamine, but to date there is little evidence that DAO impacts on the dopamine system. To address this issue, we measured the electrophysiological properties of dopaminergic (DA) and non‐DA neurons in the ventral tegmental area (VTA) of anaesthetised DAO knockout (DAO−/−) and DAO heterozygote (DAO+/−) mice as compared with their wild‐type (DAO+/+) littermates. Genotype was confirmed at the protein level by western blotting and immunohistochemistry. One hundred and thirty‐nine VTA neurons were recorded in total, and juxtacellular labelling of a subset revealed that neurons immunopositive for tyrosine hydroxylase had DA‐like electrophysiological properties that were distinct from those of neurons that were tyrosine hydroxylase‐immunonegative. In DAO−/− mice, approximately twice as many DA‐like neurons fired in a bursting pattern than in DAO+/− or DAO+/+ mice, but other electrophysiological properties did not differ between genotypes. In contrast, non‐DA‐like neurons had a lower firing rate in DAO−/− mice than in DAO+/− or DAO+/+ mice. These data provide the first direct evidence that DAO modulates VTA DA neuron activity, which is of interest for understanding both the glutamatergic regulation of dopamine function and the therapeutic potential of DAO inhibitors. The increased DA neuron burst‐firing probably reflects increased availability of d‐serine at VTA NMDA receptors, but the site, mechanism and mediation of the effect requires further investigation, and may include both direct and indirect processes.